Les notables voconces au Haut-Empire - Bernard Rémy; Nicolas Mathieu (Gallia)
Rare literary sources and epigraphy have enabled us to list 178 Vocontii “notables” and members of their families. According to their dignitas they can be divided into five different hierarchical groups: honestiores, priests (except flamines and flaminicae of the imperial cult), local honorati, municipal honorati and “imperial” honorati. Honestiores are significantly fewer than honorati and évergètes (75 out of 178 “notables”). Women (42 in number) are also far behind men (136). Our documentation covers a long period, from 66-65 BC to the second half of the 3rd c. AD, but more than fifth of the inscriptions cannot be dated. 31 “notables” are attested outside their civitas; the rest of them are mainly mentioned in texts found in Luc-en-Diois (Drôme), Die (Drôme) and Vaison-la-Romaine (Vaucluse). Other small towns and rural areas are far less represented. It can be assumed, however, that this privileged society derived the bulk of their wealth from their lands. Most of them were Roman citizens whose names are evidence of their will to integrate the Latin world and Romanitas. The same is true of the 25 peregrini. Their participation in local, municipal and “imperial” life remained constant throughout the Early Empire.